CALCULATION OF THE PARAMETERS OF CLEANER FROM COTTON FINE WASTE - Хайдаров Бахтиёр Абдуллажон ўғли (Web of Journals Publishing, 2024)
The article presents the construction scheme and principle of operation of the machine for cleaning cotton from small waste with drums with multi-faceted piles. Based on theoretical studies, the results of justification of cleaner parameters are given. Recommendations for the use of a cotton cleaner from small impurities recommended for production are given.
Keywords: Cotton raw material, small waste, cleaner, piles, drum, angle of deviation, mass, inertia, friction, coordinate, force, bond, displacement, velocity, acceleration.